PENGARUH RETURN ON ASSETS DAN CURRENT RATIO TERHADAP HARGA SAHAM PERUSAHAAN PT. ULTRA JAYA MILK.Tbk - Eneng Rochmah; Herry Winarto (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
This research was conducted to describe the Return on Assets (ROA) and Current ratio (CR) of PT Ultra jaya mil Tbk's stock prices partially and simultaneously. The research method in this study uses simple regression analysis techniques, multiple regression, assumption test, test F and T. test simultaneously obtained that Return On Assets and Current Ratio to Investment Prices and Returns on Assets Against Stock Prices have a positive and significant effect